DIGITAL TECHNOLOGIES AND THEIR ROLE IN THE IMPLEMENTATION OF MANAGEMENT DECISIONS AT THE LOCAL LEVEL - Vozniak, Halyna; Kharchev, Oleh (Socio-economic relations in the digital society, 2024)
The purpose of the article is to deepen the theoretical foundations and substantiate the impact of digital technologies on local decision-making in the context of modern challenges. Based on the methods of systematic and comparative analysis, synthesis and generalization, the following conclusions and results were obtained: a) the theoretical foundations were deepened by specifying the understanding of the essence of the concept of “digital technologies”; b) the problems and challenges of introducing digital technologies into the practice of local government were diagnosed; c) the directions of development of digital technologies and their impact on local decision-making were substantiated. It is argued that citizens’ growing need for quality public services necessitates enhancing the digitalization of management processes at the local level, which is a key tool for creating more open, adaptive, and effective governance. It is proved that the introduction of modern digital technologies in the process of making managerial decisions at the local level will contribute to the smooth functioning of systems, optimization of resources, cost reduction and, most importantly, strengthening the interaction between the authorities and citizens. Digitalization, based on the use of modern innovative tools such as electronic document management, online platforms, data analytics systems, artificial intelligence technologies, blockchain, smart cities, open data, etc., is a key factor in sustainable development, ensuring effective governance, citizen participation in decision-making, and the competitiveness of the state in the global context. The practical significance of the study is seen in the development of proposals to overcome challenges and minimize risks, as well as the development of possible areas for strengthening digitalization processes at the local level.